Independent and interdependet self-construal on communication styles among the Malaysian young adults - Azmi, Syasya Firzana; Marof, Aini Azeqa; Abdullah, Haslinda; Zarimohzzabeih, Zeinab (Human Resource Management Academic Research Society, 2023)
Understanding the relationship between self-construal and communication style is important because it allows for a better comprehension of how cultural values and individual perspectives shape communication behaviors. This leads to a more effective cross-cultural interactions and improved mutual understanding. Therefore, this study was conducted to determine the relationship between self-construal and communication styles among public university students in Klang Valley. A total of 380 students have participated in this study with a self-administered questionnaire was used in collecting the data. The results revealed that the majority of the respondents had moderate level independent self-construal and interdependent self-construal meanwhile majority of the respondents had high level of communication styles. Independent self-construal was correlated with friendly, impression leaving, relaxed, argumentative, attentive, animated, dramatic, open, and dominant, meanwhile, interdependent self-construal was correlated with friendly, impression leaving, argumentative, attentive, animated, open and dominant. Moreover, the regression analysis showed that interdependent self-construal was the strongest predictor in all types of communications. From this study, self-construal has a significant impact on communication styles, influencing how individuals express themselves, interpret messages, and engage in interpersonal interactions within their cultural context. This knowledge can help minimize miscommunication, enhance collaboration, and promote successful interpersonal relationships in diverse cultural contexts.